2013
DOI: 10.1182/blood-2012-06-436691
|View full text |Cite
|
Sign up to set email alerts
|

The constitutive androstane receptor is a novel therapeutic target facilitating cyclophosphamide-based treatment of hematopoietic malignancies

Abstract: Key Points• The constitutive androstane receptor as a novel molecular target can facilitate cyclophosphamide-based chemotherapy.Cyclophosphamide (CPA) is one of the most widely used chemotherapeutic prodrugs that undergoes hepatic bioactivation mediated predominantly by cytochrome P450 (CYP) 2B6. Given that the CYP2B6 gene is primarily regulated by the constitutive androstane receptor (CAR, NR1I3), we hypothesize that selective activation of CAR can enhance systemic exposure of the pharmacologically active 4-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Wang et al showed that selective activation of CAR and subsequent induction of CYP2B6 in human primary hepatocytes enhanced the bioactivation of chemotherapeutic prodrug cyclophosphamide. Therefore activator of human CAR might improve the efficacy of cyclophosphamide-based chemotherapy [52]. …”
Section: Role Of Car In Human Diseasesmentioning
confidence: 99%
“…Wang et al showed that selective activation of CAR and subsequent induction of CYP2B6 in human primary hepatocytes enhanced the bioactivation of chemotherapeutic prodrug cyclophosphamide. Therefore activator of human CAR might improve the efficacy of cyclophosphamide-based chemotherapy [52]. …”
Section: Role Of Car In Human Diseasesmentioning
confidence: 99%
“…As a prodrug, CPA is converted in the body to its active form mainly by CYP2B6. Because CYP2B6 is a major target of CAR, in hepatocyte co-cultures with a leukemia cell line, CAR activation (with agonist CITCO) can enhance CPA-based antitumor activity and apoptosis [120] by increasing the availability of the active form. Recently, the common chemotherapeutic paclitaxel was used to determine that CAR agonists modestly increase paclitaxel-induced tumor depletion in 5 human lung cancer cell lines [121].…”
Section: Biological Significance Of Carmentioning
confidence: 99%
“…Human primary hepatocytes seeded 7.5 Â 10 4 cells/well in 96-well plates were cultured for 48 hours before treatment with BSEP inhibitors at previously indicated concentrations. A typical 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay was carried out as described previously (Wang et al, 2013). Cell viability was expressed as percent of vehicle control (0.1% DMSO).…”
Section: Methodsmentioning
confidence: 99%